Empreendedorismo na gestão universitária pública de enfermagem: entraves e estratégias - Fernanda Hannah da Silva Copelli; Alacoque Lorenzini Erdmann; José Luís Guedes dos Santos; Gabriela Marcellino de Melo Lanzoni; Selma Regina de Andrade (Universidade Federal do Ceará, 2017)
Objective: to understand the obstacles to entrepreneurship in the public university management of nursing and the strategies to overcome them. Methods: it is a qualitative research with the theoretical-methodological contribution of Grounded Theory. Intensive interviews were conducted with 27 participants divided into three sample groups. Results: the obstacles to entrepreneurship in the university public nursing management are the bureaucratic management model, the lack of resources and infrastructure, the multiplicity of teaching activities, the lack of knowledge in entrepreneurship and university management and the difficulty in managing people. The strategies are the dissemination of entrepreneurship, the search for theoretical knowledge and the incentive to entrepreneurship in the academic community. Conclusion: the obstacles to entrepreneurship in the university public nursing management are organizational and personal and the strategies are education and dissemination of entrepreneurship.